IMPROVING THE STUDENT’S ABILITY TO USE GRAMMAR THROUGH THE TRANSLATION METHOD AT SMP NEGERI 10 MEDAN - Lidia Afriani Sitanggang; Lastri Wahyuni Manurung; Fenty Debora Napitupulu (Jurnal Scientia, 2023)
This research aimed to find out the improvement of students’ grammar mastery by using translation method activities. This research was conducted by using Classroom Action Research (CAR). The sample in this research were the second grades of SMP NEGERI 10 MEDAN which consist of 32 students. This research conducted in two cycles. Each cycle consisted of planning, action, observation and reflection. Both cycles were carried out in two meetings. The data was collected by quantitative data and qualitative data. The quantitative data was taken from the results of grammar scores in pre-test, post-test I and post-test II. While qualitative data was taken from questionnaire and observation results. The results showed that there was an improvement on the students’ grammar mastery. It can be seen from the mean score of the students’ pre-test which was 40,78 and the mean score in post-test I was 64,53. In post-test II, the mean score increased to 81,40. In addition, there were 2 students or 6,25% from 32 students passed the Minimum Completeness Criteria (KKM) in the pre-test, while in post-test I there were 12 students or 37,5% from 32 students passed the KKM and 26 students or 81,25% from 32 students passed the KKM. Furthermore, the results of observation and questionnaire showed that students gave positive responses to the use of translation method in learning. Translation method is able to improve students’ grammar mastery.